Implementasi Metode Praktikum pada Pembelajaran Fiqh Kelas V di MI Maidanuttullab Waung Baron Kabupaten Nganjuk - Silvia Halimatul Ma’rifah; Badrus; Yasin Nurfalah (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
How is the implementation of the practicum method in learning fiqh at MI Maidanuttullab Waung Baron Nganjuk? The application of the practical method in class V Fiqh learning is appropriate. Because this method is believed to be the right method in doing things that are real. Madrasas as formal educational institutions, systematically plan various kinds of learning. Fiqh is one of the fields of science in Islamic law that specifically discusses the law that regulates various aspects of human life. Both personal life, society, and human relationships with their creators. In carrying out religious activities, humans use Fiqh as a guide. Such as taharah, prayer, zakat, fasting, Hajj and Umrah procedures. Therefore, in the world of education, developing the potential of students, both cognitive, affective, and psychomotor aspects is the task of educators and educators are expected to be able to seek students to be able to gain learning experiences and practices from the learning process that is realized. This research is a research with a qualitative descriptive approach. Data collection techniques using observation, interviews, and documentation. Data analysis technique uses data reduction, qualitative data presentation, and drawing conclusions. Meanwhile, in testing the validity of the data using Extended Participation, increasing persistence, and peer checking through discussion.